Characterisation of fatigue damage process in carbon fibre reinforced composites - Fun, Ronnie. (2012)
The use of carbon fibre reinforced composites (CFRP) is ever increasing in the world today, especially in the automobile and aerospace industries. Porosity is a very common problem in the manufacture of CFRP. As such, research has to be done in this area to determine how the presence of porosity voids influences the properties of CFRP. CFRP is a new material, and not much research has been done regarding the fatigue properties of CFRP with porosity. This project aims to fill that gap by serving as a stepping stone upon which future research in this topic can base their research upon.